UTILIZATION OF OCEANOGRAPHIC DATA IN SUPPORTING THE NATIONAL DEFENSE AND SECURITY ANALYSIS IN TERMS OF HANDLING THE ILLEGAL FISHING IN INDONESIA - Noir P. Purba; Marine Kenzi Martasuganda; Dian Adrianto (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
One of the issues in Indonesia’s maritime security is Illegal, Unreported, and Unregulated (IUU) fishing. This research focuses on how to reduce illegal fishing using oceanographic data to support agencies concerned about ocean security. The main data collected from in-situ sampling by NOAA and to support the analysis, data also collected from several reports and published articles. The results showed that many station data already stored in the global database especially in boundary seas of Indonesia. However, the data is not continuously monitored. These data (temperature, salinity, and ocean currents) also correlate with fishing locations, especially in the boundary area. Furthermore, the oceanographic data with high performance of instrument could predict the fishing locations and the changing ocean. In conclusion, ocean databases and real-time data from instruments could support the agencies to protect Indonesia’s water.